Development and validation of the Portuguese version of the Eating Disorder Diagnostic Scale - Santos, Isabel F. (2018)
This article presents the psychometric properties for the Portuguese population of a brief self-report scale for diagnosing anorexia nervosa (AN), bulimia nervosa (BN), and binge-eating disorder (BED): the Eating Disorder Diagnostic Scale (Stice et al., 2000).Method: To study the psychometric properties of EDDS, an exploratory factor analysis was done first, followed by a confirmatory factor analysis.Results: The results of the exploratory factor analysis revealed the existence of three components and the confirmatory factor analysis showed a structure with three latent variables (Body and Weight Concerns, Binge Eating Behaviour and Compensatory Behaviours), with a second order variable (Eating Disorder Symptoms) with a good adjustment fit. The internal consistency and the test-retest correlations revealed an adequate reliability and the inter-correlations of the EDDS subscales with other measures of the same and different constructs, supported the convergent and discriminant validity of this measure.Conclusions: Summing up, the EDDS seems to be a useful measure to assess eating disorders symptomatology in the Portuguese population. (C) 2018 Sociedad Espanola para el Estudio de la Ansiedad y el Estres - SEAS. Published by Elsevier Espana, S.L.U. All rights reserved.